INTERPERSONAL COMMUNICATION CHALLENGES ARISING FROM KNOWLEDGE HIDING IN PRE-SERVICE STUDENT TEACHERS - Saini, Shilpa; Kaushal, Rekha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Knowledge sharing is a crucial aspect of an educational organization. It assists in the growth and development of an institution as a whole. But recently, the topic of knowledge hiding, where people suppress information or expertise, has emerged. Knowledge hiding in education, specifically among pre-service teachers, has serious implications for student learning as well as professional growth. This article examines the prevalence and predictors of knowledge hiding behavior among Pre-Service student teachers and its impact on the quality of interpersonal interactions among peers, mentors, and students in teacher education program. Data collection uses survey method with questionnaire as instrument, and sample was Pre-Service student teachers in teacher educations programs. Knowledge hiding behavior are not rare among Pre-Service student teachers, with competition, fear of judgement, and lack of trust being among the reasons why they choose to withhold information. The present study points out that knowledge hiding can impede effective communication and cooperation among student teachers, jeopardizing their learning experience and professional development. The research supports the teacher education institutions to combat knowledge hiding behavior and encourage an open collaboration and knowledge sharing culture. 173 Pre-Service student teachers were sampled. Questionnaire was designed which was again transformed into google form and then distributed to various education institutions of north India. Level of knowledge hiding behaviour was calculated based on responses. If the causes of knowledge hiding behavior are known, then intervention is possible to promote an open and cooperative learning culture.